Pharmacokinetics and Tolerability of a Single Dose of Semaglutide, a Human Glucagon-Like Peptide-1 Analog, in Subjects With and Without Renal Impairment - Marbury, Thomas C.; Flint, Anne; Jacobsen, Jacob B.; Derving Karsbøl, Julie; Lasseter, Kenneth (Clinical pharmacokinetics, 2017)
Background The pharmacokinetics and tolerability of semaglutide, a once-weekly human glucagon-like peptide-1 analog in development for the treatment of type 2 diabetes mellitus, were investigated in subjects with/without renal impairment (RI). Methods Fifty-six subjects, categorized into renal function groups [normal, mild, moderate, severe, and end-stage renal disease (ESRD)], received a single subcutaneous dose of semaglutide 0.5 mg. Semaglutide plasma concentrations were assessed ≤480 h post-dose; the primary endpoint was the area under the plasma concentration–time curve from time zero to infinity. Results Semaglutide exposure in subjects with mild/moderate RI and ESRD was similar to that in subjects with normal renal function. In subjects with severe RI, the mean exposure of semaglutide was 22% higher than in subjects with normal renal function, and the 95% confidence interval (1.02–1.47) for the ratio exceeded the pre-specified limits (0.70–1.43). When adjusted for differences in sex, age, and body weight between the groups, all comparisons were within the pre-specified clinically relevant limits. Across RI groups there was no relationship between creatinine clearance (CL CR ) and semaglutide exposure, or between CL CR and semaglutide maximum plasma drug concentration ( C max ). Hemodialysis did not appear to affect the pharmacokinetics of semaglutide. No appreciable changes in safety parameters or vital signs and no serious adverse events were noted. One subject with severe RI reported two major hypoglycemic events. Conclusion When adjusted for differences in sex, age, and body weight, semaglutide exposure was similar between subjects with RI and subjects with normal renal function. Semaglutide (0.5 mg) was well-tolerated. Dose adjustment may not be warranted for subjects with RI. ClinicalTrials.gov identifier NCT00833716.